Effectiveness of the Elsimil Program Supported by Family Assistance Teams on Knowledge, Attitudes, and Nutritional Expectations Among Prospective Brides: A Quasi-Experimental Study - Siti Maryam Syafitri; Nikmah Utami Dewi (Journal of Community Nutrition Intervention, 2026)
The Elsimil application (Electronic Ready for Marriage and Pregnancy) was developed as a screening, education, and assistance tool for prospective brides. This study aimed to analyze the effectiveness of the Elsimil application combined with support from the Family Assistance Team (Tim Pendamping Keluarga/TPK) on nutritional knowledge, attitudes, and expectations among prospective brides in Palu City. This study employed a quantitative approach using a quasi-experimental design with a non-randomized control group and a pretest–posttest design. The sample size was calculated using the formula for testing differences between two proportions, yielding a total of 54 respondents. Participants were randomly assigned to an intervention group (n = 27) and a control group (n = 27). Baseline data revealed significant differences in age and education level, with the control group being older and more highly educated. The intervention group received education through the Elsimil application, accompanied by TPK support, while the control group received conventional nutrition education using a booklet. Data were analyzed using the Mann–Whitney test and were supplemented with consideration of baseline confounders. Statistical analysis showed no significant differences between the intervention and control groups in terms of nutritional knowledge (p = 0.162), attitudes (p = 0.340), or nutritional expectations (p = 0.330). While the Elsimil application provides a digital platform for education, technical barriers and baseline demographic imbalances, particularly in education levels, significantly influenced the outcomes. Improvements in user interface design, offline accessibility, and targeted facilitator training are needed to enhance the application's effectiveness compared to traditional media.